Review of psychological stress on oocyte and early embryonic development in female mice - Qiu-Yue Zhai; Jun-Jie Wang; Yu Tian; Xiaofang Liu; Zhenhua Song (BMC, 2020)
Abstract Psychological stress can cause adverse health effects in animals and humans. Accumulating evidence suggests that psychological stress in female mice is associated with ovarian developmental abnormalities accompanied by follicle and oocyte defects. Oocyte and early embryonic development are impaired in mice facing psychological stress, likely resulting from hormone signalling disorders, reactive oxygen species (ROS) accumulation and alterations in epigenetic modifications, which are primarily mediated by the hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-ovarian (HPO) axes. The present evidence suggests that psychological stress is increasingly becoming the most common causative factor for female subfertility. Here, we review recent progress on the impact of psychological stress on female reproduction, particularly for oocyte and early embryonic development in female mice. This review highlights the connection between psychological stress and reproductive health and provides novel insight on human subfertility.